Metabolic profiling, in-situ spatial distribution, and biosynthetic pathway of functional metabolites in Dendrobium nobile stem revealed by combining UPLC-QTOF-MS with MALDI-TOF-MSI - Liu, Qingling; Huang, Yuan; Linghu, Chu; Xiao, Jianfen; Gu, Ronghui (Frontiers in Plant Science, 2023)
The stem of Dendrobium nobile Lindl. (Orchidaceae), called “Shihu” in traditional Chinese medicine, is a well-known medicinal and edible plant material in China. It is used as an antipyretic, analgesic, and tonic to nourish the stomach and Yin (i.e., to improve the production of body fluids). These therapeutic properties are attributed to its alkaloids, sesquiterpenoids, bibenzyls, fluorenones, and phenanthrenes. However, a comprehensive understanding of these metabolites and their spatial distribution in stems is lacking. In this study, ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) was performed to obtain detailed metabolites information about D. nobile stems. Then, the spatial distributions of diverse metabolites, including alkaloids and sesquiterpenoids, were characterized and visualized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry imaging (MALDI-TOF-MSI). Based on the spatial and metabolic profiling data, sesquiterpene alkaloid dendrobine was chosen for the exhaustive study of a biosynthetic pathway in D. nobile. This is the first report on mass spectrometry imaging for Dendrobium species. As a result, critical bioactive metabolites such as 11 alkaloids, 10 sesquiterpenes, and 13 other metabolites were putatively identified and relatively quantified. The identified alkaloids were distributed in the parenchyma or vascular bundle, and sesquiterpenes were present in all regions of the stem with higher abundance in the vascular bundle and cuticle, or in the cuticle and epidermis. The biosynthetic pathway and accumulation pattern of dendrobine in D. nobile stem were also proposed. Our findings not only provided a critical methodology for the thorough understanding of physiological changes in metabolites and precise utilization of D. nobile stem, but also displayed an effective strategy for insight into the biosynthesis of bioactive metabolites in plants.